Analysis of Marginal Bone Loss and Residual Ridge Resorption in Conventionally Loaded Single and Two Implant Supported Overdentures - Gill, Harvindersingh; Nagpal, Archana; Vaidya, Sharad; Jindal, Vikas; Sharma, Pratibha (International Journal Of Drug Research And Dental Science, 2021)
Purpose: The aim of this study was to analyze the marginal bone loss and residual ridge resorption in patients wearing single and two implant-supported overdentures. Materials and methods: This study was conducted on 20 edentulous patients between 50-75 years of age who have been completely edentulous for a period of at least one year or more. Patients were divided into two groups: Group-A in which two implants of size 3.75x13mm were placed in B and D position and ball abutments were attached to make an overdenture; in Group-B patients, a single implant at position C was placed and overdenture was made with ball abutments. Crestal bone loss was recorded around the margins in both the groups and residual ridge resorption was calculated in the mandibular posterior region using Wical And Swoope method. The data collected were compared for analysis using the Man-Whitney U test. Results: For 2-IOD overall mean crestal bone loss for one year was 0.15± 0.03cmand for S-IOD it was 0.14 ± 0.03cm. The significance value was calculated to be 0.518 and U=41.5 which was found to be non-significant. Difference in residual ridge resorption was also found to be non-significant in both the groups with the significance value of 0.284 and U=36. Conclusion: The scope of the single implant-retained overdentures can be a promising alternative for patients with an atrophic mandible, systemically compromised patients with financial difficulties.